2011
DOI: 10.1111/j.1365-263x.2011.01136.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral microflora in infants delivered vaginally and by caesarean section

Abstract: BACKGROUND.  Early in life, vaginally delivered infants exhibit a different composition of the gut flora compared with infants delivered by caesarean section (C-section); however, it is unclear whether this also applies to the oral cavity. AIM.  To investigate and compare the oral microbial profile between infants delivered vaginally and by C-section. DESIGN.  This is a cross-sectional case-control study. Eighty-four infants delivered either vaginally (n = 42) or by C-section (n = 42) were randomly selected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 21 publications
1
32
1
Order By: Relevance
“…Three studies rated weak [24] to moderate [25, 30] in quality assessment reported significant lower frequency of S. mutans detection among infants born by cesarean section compared with those vaginally delivered but only among younger groups (2 days, 1 month, and 3 months old). Instead, 6 studies that were considered to have moderate [14, 27, 28, 31] to strong [21, 23] methodological quality reported no significant differences in prevalence of oral colonization by S. mutans between groups by mode of delivery (Table 2). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies rated weak [24] to moderate [25, 30] in quality assessment reported significant lower frequency of S. mutans detection among infants born by cesarean section compared with those vaginally delivered but only among younger groups (2 days, 1 month, and 3 months old). Instead, 6 studies that were considered to have moderate [14, 27, 28, 31] to strong [21, 23] methodological quality reported no significant differences in prevalence of oral colonization by S. mutans between groups by mode of delivery (Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…Eight studies [14, 21, 23, 25, 27, 28, 30, 31] showed results on differences between groups by the mode of delivery in the prevalence of children with S. mutans (or mutans streptococci) and/or S. salivarius . Results were stratified according to the children’s age and summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations